Artificial intelligence and machine learning applications for the imaging of bone and soft tissue tumors - Sabeghi, Paniz; Kinkar, Ketki K.; Castaneda, Gloria del Rosario; Eibschutz, Liesl S.; Fields, Brandon K. K.; Varghese, Bino A.; Patel, Dakshesh B.; Gholamrezanezhad, Ali (Frontiers in Radiology, 2024)
Recent advancements in artificial intelligence (AI) and machine learning offer numerous opportunities in musculoskeletal radiology to potentially bolster diagnostic accuracy, workflow efficiency, and predictive modeling. AI tools have the capability to assist radiologists in many tasks ranging from image segmentation, lesion detection, and more. In bone and soft tissue tumor imaging, radiomics and deep learning show promise for malignancy stratification, grading, prognostication, and treatment planning. However, challenges such as standardization, data integration, and ethical concerns regarding patient data need to be addressed ahead of clinical translation. In the realm of musculoskeletal oncology, AI also faces obstacles in robust algorithm development due to limited disease incidence. While many initiatives aim to develop multitasking AI systems, multidisciplinary collaboration is crucial for successful AI integration into clinical practice. Robust approaches addressing challenges and embodying ethical practices are warranted to fully realize AI's potential for enhancing diagnostic accuracy and advancing patient care.